Exponential of Sum/Complex Numbers/General Result
Theorem
Let $m \in \N_{>0}$ be a natural number.
Let $z_1, z_2, \ldots, z_m \in \C$ be complex numbers.
Let $\exp z$ be the exponential of $z$.
Then:
- $\ds \map \exp {\sum_{j \mathop = 1}^m z_j} = \prod_{j \mathop = 1}^m \paren {\exp z_j}$
Corollary
Let $m \in \Z_{>0}$ be a positive integer.
Let $z \in \C$ be a complex number.
Let $\exp z$ be the exponential of $z$.
Then:
- $\ds \exp \paren {m z} = \paren {\exp z}^m$
Proof
The proof proceeds by induction.
For all $m \in \N_{>0}$, let $\map P m$ be the proposition:
- $\ds \map \exp {\sum_{j \mathop = 1}^m z_j} = \prod_{j \mathop = 1}^m \paren {\exp z_j}$
$\map P 1$ is the case:
\(\ds \map \exp {\sum_{j \mathop = 1}^1 z_j}\) | \(=\) | \(\ds \exp z_j\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \prod_{j \mathop = 1}^1 \paren {\exp z_j}\) |
Thus $\map P 1$ is seen to hold.
Basis for the Induction
$\map P 2$ is the case:
- $\map \exp {z_1 + z_2} = \paren {\exp z_1} \paren {\exp z_2}$
This is proved in Exponential of Sum: Complex Numbers.
Thus $\map P 2$ is seen to hold.
This is the basis for the induction.
Induction Hypothesis
Now it needs to be shown that if $\map P k$ is true, where $k \ge 1$, then it logically follows that $\map P {k + 1}$ is true.
So this is the induction hypothesis:
- $\ds \map \exp {\sum_{j \mathop = 1}^k z_j} = \prod_{j \mathop = 1}^k \paren {\exp z_j}$
from which it is to be shown that:
- $\ds \map \exp {\sum_{j \mathop = 1}^{k + 1} z_j} = \prod_{j \mathop = 1}^{k + 1} \paren {\exp z_j}$
Induction Step
This is the induction step:
\(\ds \map \exp {\sum_{j \mathop = 1}^{k + 1} z_j}\) | \(=\) | \(\ds \map \exp {\sum_{j \mathop = 1}^k z_j + z_{k + 1} }\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \map \exp {\sum_{j \mathop = 1}^k z_j} \exp z_{k + 1}\) | Basis for the Induction | |||||||||||
\(\ds \) | \(=\) | \(\ds \prod_{j \mathop = 1}^k \paren {\exp z_j} \exp z_{k + 1}\) | Induction Hypothesis | |||||||||||
\(\ds \) | \(=\) | \(\ds prod_{j \mathop = 1}^{k + 1} \paren {\exp z_j}\) |
So $\map P k \implies \map P {k + 1}$ and the result follows by the Principle of Mathematical Induction.
Therefore:
- $\forall m \in \N_{>0}: \ds \map \exp {\sum_{j \mathop = 1}^m z_j} = \prod_{j \mathop = 1}^m \paren {\exp z_j}$
$\blacksquare$
Sources
- 1960: Walter Ledermann: Complex Numbers ... (previous) ... (next): $\S 2$. Geometrical Representations